PENGARUH TECHNOLOGY ACCEPTANCE MODEL (TAM) TERHADAP NIAT BELI ULANG ONLINE DI KOTA DENPASAR - Sandra Dewi, Putu Devi; Santika, I Wayan (E-Jurnal Manajemen; Vol 7 No 8 (2018)DO - 10.24843/EJMUNUD.2018.v07.i08.p04, 2018)
This study aims to determine the effect of perceived ease of use, perceived usefulness, perceived enjoyment, perceived risk, prior online shopping experience of the intention to buy online in Denpasar. Respondents are internet users in Denpasar City who have been shopping online. The method of determining the sample used is purposive sampling with the number of samples as much as 125 respondents. The result of this research is positive and significant influence perceived ease of use, perceived usefulness, perceived enjoyment, and prior online shopping experience towards online shopping intention in Denpasar city and there is negative and significant influence perceived risk toward online shopping intention in Denpasar City. This research can serve as a reference for learning and research on methods of Theory Acceptance Model and online shopping, related to marketing management science.